ZnO and MgO as inducers of spinel-like phase formation on alumina-based castables. Issue 15 (December 2022) - Borges, O.H.; Sardelli, J.A.P.; Pagliosa Neto, C.; da Luz, A.P.; Pandolfelli, V.C.
Abstract: Environmental issues regarding Cr 6+ formation lead to replacing chrome-containing refractories with greener alternatives. MgO-containing compositions have been extensively investigated for this purpose, however, few studies evaluated the likelihood of using other chemical elements as inducers of spinel-like phase formation in refractory castables. In this study, the addition of zincite in alumina-based castables was evaluated and compared with its MgO-counterpart. In-situ elastic modulus, assisted sinterability and differential scanning calorimetry pointed out that the gahnite (ZnAl2 O4 ) formation took place at lower temperatures (∼ 1100 °C) than MgAl2 O4 (∼ 1300 °C). On one hand, this feature induces anticipated strengthening of the Zn-containing compositions, giving rise to the possibility of firing these compositions at lower temperatures. On the other, the faster kinetics of gahnite formation led to a significant Kirkendall effect, changing the morphology of the pores created during sintering, which became preferentially located at the interface of alumina aggregates, negatively affecting some mechanical properties of the castable.